Neuroproprioceptive facilitation techniques. Practical applications for the upper limb - IANC, Dorina; DEAC, Anca (2020)
Proprioceptive neuromuscular facilitation (PNF) uses the body’sproprioceptive system to ease or inhibit muscle contraction. These techniquesare based on Sherrington’s reciprocal inhibition, innervation and irradiationprinciples (1).PNF techniques were developed in the 1940-1950 and they are theresult of Kabat’s, Knott’s and Voss’s work (1, 2). They combine the researchof functional movement with theories of motor development, motor control,motor learning and neurophysiological theories (3).Harman Kabat first used the PNF techniques on young people withcerebral palsy and other neurological disorders (2, 4).D. Voss defines neuroproprioceptive facilitation as a promotion oracceleration method of the neuromuscular system’s response byproprioceptors’ stimulation. The muscles must work in synergy in order toachieve the movement. This requires that the muscles should have the reflexcapacity of contraction and relaxation to perform the basic movement. Thebasis of functional training is the ability to create a balance between mobilityand stability (5).